(untitled) (American Journal of Education and Technology, 2023)
This study aimed to identify the learning styles and learning strategies among students under the Bachelor of Secondary Education major in English Program, College of Arts and Sciences and Teacher Education, Saint Joseph’s College of Baggao Inc. Descriptive research design was used in the study. Data from the 155 participants were gathered using the Perceptual Learning Styles Preference Questionnaire (PLSPQ) by Reid (1984) and the Strategy Inventory Language Learning (SILL) by Oxford (1990). Frequency, percentages, mean score, standard deviation, and Pearson Correlation were used in analyzing the data. Findings of the study showed that most of the participants are fourth year students, speak Ilocano and females. They studied in a public secondary school. It also showed that most of the participants used indirect strategies which include metacognition, being the most used strategy, followed by social and affective strategies. Furthermore, auditory learning is typically preferred, followed by kinesthetic and visual learning. Additionally, analysis shows a substantial correlation between the respondents’ profile factors and their language learning approaches and learning preferences. The study concludes that rather than requiring the cerebral processing of language learning, the participants promote language learning through focusing, planning, evaluating, seeking opportunities, reducing fear, boosting cooperation, and developing empathy. The students’ language learning methods and learning preferences are unaffected by the participant profiles.